Development of a chamber for low temperatures simulation - Filho, João Manetti; Caramori, Paulo Henrique (Pesquisa Agropecuaria Brasileira, 2014)
A small chamber to simulate low temperatures was developed, utilizing the following equipments and materials: 1. Portable cooling unit. 2. A box made of galvanized iron sheet measuring 80cm x 40cm x 40cm, recovered with a layer of a heat insulator. 3. Circulating pump of 0.12 c.v. 4. Potentiometric temperature recorder with thermocouple sensors. 5. Ethanol solution at 19%, enough to obtain temperatures near -10ºC. Temperature differences inside the box were not higher than 0,2°C. Plants subjected to cold temperatures were placed inside a plastic bag, in order to avoid direct contact with the ethanol solution. Tests carryed out with young coffee plants showed that this chamber is suitable for cold tolerance studies.